(untitled) - Champy, James (New York, 1995)
The coauthor of Reengineering the Corporation explains how to transform the principles and practices of management to adapt to a changing corporate environment, discussing essential reforms in culture, attitude, organization, and hierarchy.
Keywords: Industrial management,Organizational change,Executives,Leadership; United states,United states,United states